Interspecies and intergender differences in acute toxicity of K-oximes drug candidates - Jaćević, Vesna; Nepovimova, Eugenie; Kuča, Kamil (Chemico-biological interactions, 2019)
K-oximes were developed as modern drug candidates acting as AChE reactivators. In this study, it has been investigated which interspecies and intergender differences changes could be observed in Wistar rats and Swiss mice, both genders, after the treatment with increasing doses of selected acetylcholinesterase reactivators - asoxime, obidoxime, K027, K048, and K075. After the 24 h, a number of died animals was counted and the median lethal dose (LD50) for each oxime was calculated. By using the intramuscular route of administration, asoxime and K027 had the least toxicity in female rats (640.21 mg/kg and 686.08 mg/kg), and in female mice (565.75 mg/kg and 565.74 mg/kg), respectively. Moreover, asoxime and K027 showed 3, 4 or 8 times less acute toxicity in comparison to K048, obidoxime and K075, respectively. Beyond, K075 had the greatest toxicity in male rats (81.53 mg/kg), and in male mice (57.34 mg/kg), respectively. Our results can help to predict likely adverse toxic effects, target organ systems and possible outcome in the event of massive human overexposure, and in establishing risk categories or in dose selection for the initial repeated dose toxicity tests to be conducted for each oxime.
Keywords: Animals; Acetylcholinesterase; Rats; Female; Lethal Dose 50; Rats, Wistar; Prodrugs; ženské pohlaví; oximy; K-oximes; LD50; Mice; prekurzory léčiv; myši; Oximes; Male; Obidoxime Chloride; acetylcholinesterasa; Toxicity Tests, Acute; reaktivátory cholinesterasy; LD(50); obidoxim chlorid; krysa rodu Rattus; Acute toxicity; zvířata; mužské pohlaví; testy akutní toxicity; Cholinesterase Reactivators; potkani Wistar